Durability of sustained virological response to glecaprevir/pibrentasvir and resistance development: A long‐term follow‐up study. (14th March 2022) - Poordad, Fred; Felizarta, Franco; Yao, Betty B.; Overcash, J. Scott; Hassanein, Tarek; Agarwal, Kosh; Gane, Edward; Shaw, David; Waters, Michael; Krishnan, Preethi; Topp, Andrew; Burroughs, Margaret; et al.
Abstract: Background and Aims: This study aimed to determine durability of sustained virologic response (SVR) in hepatitis C virus‐infected participants treated with glecaprevir‐ and/or pibrentasvir‐containing regimens. Methods: M13‐576, a rollover study, evaluated the durability of SVR in a follow‐up period of approximately 3 years after hepatitis C virus genotype 1–6‐infected participants received a glecaprevir‐ and/or pibrentasvir‐containing regimen in previous phase 2/3 clinical trials. The primary efficacy endpoint was the percentage of participants maintaining SVR and the percentage of participants experiencing relapse or reinfections. Resistance‐associated substitutions and safety outcomes related to liver progression were also assessed. Results: Of 384 participants enroled, 377 participants were included in the as‐observed population and 287 participants completed the study. In prior studies, 99.7% (376/377) of participants achieved SVR12; of those, an observed 99.5% (374/376) and 100% (286/286) completing the study, maintained SVR. After non‐responder imputation of missing data, 286/376 participants (76%) maintained SVR. The participant previously not achieving SVR was a treatment‐experienced male with compensated cirrhosis who had NS3 and NS5A substitutions at enrolment, which remained detectable for 12 months. Of the two participants not maintaining SVR, one was re‐infected and one experienced late relapse at post‐treatment week 60. Five participants (all with a fibrosis stage ≥F3) had hepatocellular carcinoma. No events were deemed related to glecaprevir/pibrentasvir. Conclusions: Glecaprevir/pibrentasvir demonstrated long‐term durability of efficacy after SVR12 was achieved. Hepatic‐related decompensation events were not seen. Owing to low incidence of virologic failure, conclusions were not drawn on persistence of resistance‐associated substitutions.